SPONTANEUS RENATURALIZATION PROCESSES OF THE VEGETATION IN THE ABANDONED FIELDS (CENTRAL ITALY) - BIONDI, EDOARDO; CASAVECCHIA, SIMONA; PESARESI, SIMONE (Annali di Botanica, 2006)
Some methodologies utilised for the analyses, with different scales, earried out in the study of the renaturalisation processes that determine in the territories that are not more utilised for agro-pastoral practices, are here described. In fact, during the last fifth teen years a progressive process of abandonment of the hilly and mountain territories. not more economically remunerative according to the present technological and market requests, have taken pIace. Therefore, in these territories. quick recovery processes by spontaneous vegetation are developing. having a great scientific and applicative importance, these processes caused, as result. a deep transformation of the plant Iandscape. These processes have been studied trough the methodologies of the phytosociological. synphytosociological and geosynphytosociological analyses in order to interpret the dynamic successions and to predict the time for the recolonisation according to diachronic studies associated to population dynamic anaIyses. To these studies are connected analyses on the architectural model of growth of Spartium junceum, species particularly active in the vegetation recovery processes, that have been canied out in CentraI ltaIy territories. These analyses allow a better comprehension of the rale of this species.